2017
DOI: 10.3390/bioengineering4020057
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Microwave-Assisted Reactions for Biodiesel Production

Abstract: The conversion of biomass into chemicals and biofuels is an active research area as trends move to replace fossil fuels with renewable resources due to society’s increased concern towards sustainability. In this context, microwave processing has emerged as a tool in organic synthesis and plays an important role in developing a more sustainable world. Integration of processing methods with microwave irradiation has resulted in a great reduction in the time required for many processes, while the reaction efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…Microwave-assisted activation produces AC with wider micropores and mesopores than the conventional products. The pore size, surface area and adsorption efficiency in both conventional and microwave activation processes are affected by activation temperature, dwell time, heating rate, type of activating agent, activation agent-feedstock ratio, particle size, inert gas flow rate, microwave power and weight of sample [75].…”
Section: A Comparison Of Activation By Microwave and The Conventional Processmentioning
confidence: 99%
“…Microwave-assisted activation produces AC with wider micropores and mesopores than the conventional products. The pore size, surface area and adsorption efficiency in both conventional and microwave activation processes are affected by activation temperature, dwell time, heating rate, type of activating agent, activation agent-feedstock ratio, particle size, inert gas flow rate, microwave power and weight of sample [75].…”
Section: A Comparison Of Activation By Microwave and The Conventional Processmentioning
confidence: 99%
“…In recent years microwave has been suggested by several researchers as a technique to reduce time and energy when producing AC from biomass [45,46]. This technique has been demonstrated in several studies but has not reached commercial scale due to various challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The scaling up potential of microwave-assisted reactions has been thoroughly reviewed by La Hoz et al (2011) [ 56 ], which reported that a microwave reactor up to 12 L was studied in organic chemistry reaction. In 2017, the use of microwave-assisted transesterification for biodiesel was still undergoing laboratory-scale experiments [ 57 ]. To date, its application has yet to be implemented at the industry level.…”
Section: Recent Stand-alone Microwave Applicationsmentioning
confidence: 99%